Monetary commitment and structural reforms: A dynamic panel analysis for transition economies - Ansgar Belke; Lukas Vogel (Research On Money in the Economy (ROME), 2012)
This paper examines the contemporaneous relationship between the exchange rate re-gime and structural economic reforms for a sample of CEEC/CIS transition countries. We investigate empirically whether structural reforms are complements or substitutes for monetary commitment in the attempt to improve macroeconomic performance. Both EBRD and EFW data suggest a negative relationship between flexible exchange rate arrangements and external liberalization. Another finding from the EFW sample is that economic libera-lisation has tended to be stronger under better macroeconomic funda-mentals, suggesting that the impact of good macroeconomic conditions as facilitating structural reforms outweighs countervailing effects in the sense of lower reform pres-sure.
Keywords: D78; E52; E61; F36; 330; Exchange rate regime; structural reform; panel data; political economy of reform; transition countries